A busca por psicoterapia durante a pandemia da COVID-19: um estudo sobre ressignificações do processo terapêutico - Vidal, Dariane Doria Ribera (2022)
This research aimed to understand the relationship between the experiences of the pandemic and the search for the therapeutic process through the narratives of people who went through the psychotherapy process during the COVID-19 pandemic. It also sought to understand how the pandemic impacted people's lives, the reasons for seeking psychotherapy for the first time, the meanings attributed to it prior to the experience and the re-significations of the therapeutic process after this experience. Data collection took place through nine on-line interviews and used the approach of analyzing the discursive practices of the narrative material produced from the dialogic interaction between participants and researcher. In order to understand this material, the following were used: full transcripts, sequential transcripts, dialogic maps and the dialogue of empirical data resulting from the interviews with the bibliographic research congruent with the research theme. The analysis results were divided into two moments. The first focused on the experiences in the pandemic. The second addressed the experience of the therapeutic process: a) the reasons that led them to seek psychotherapy, with emphasis on issues related to the pandemic: uncertainties; anxieties/depression/fears/emotions; psychology as support and indications for the process; b) how they arrived in psychotherapy; c) with whom they comment to be in psychotherapy and if there was support from the people close to them; d) the experience with the therapeutic process and e) the re-significations of the therapeutic process. In the final considerations, some reflections resulting from the concerns arising from the research were presented